Konsentrasi Hambat Minimum Ekstrak Daun Sawo (Achras Zapota L.) Terhadap Pertumbuhan Staphylococcus Aureus Secara In Vitro - Novia Yunika (Bioscience, 2017)
Sapodilla (Achras zapota L.) is a plant commonly found on the island of Java, West Sumatra and West Nusa Tenggara. Sapodilla plant contains flavonoids, saponins and tannins. In leaf the dominant are flavonoids. The content of flavonoids in the plant tissue may act as an antioxidant and antibacterial. As an alternative natural antibacterial, sapodilla leaves should also be tested minimum inhibitory concentration effective to inhibit the bacteria Staphylococcus aureus. This study aims to determine the minimum inhibitory concentration sapodilla leaf extract (Achras zapota L.) on the growth of Staphylococcus aureus. The research was conducted from January to February 2015 in the Laboratory of Microbiology  UNP. Research method is descriptive by observing turbidity levels at each test tube as well as comparison increment Optical Density (OD) before incubation and after incubation of zeroes. Sapodilla leaf extract concentration ranging from 10% - 50%, amoxilin as a positive control, and negative controls (without extract). Study results showed that the minimum inhibitory concentration of Sapodilla leaf extract on the growthbacteria present in a concentration of 50%. Keywords : Sapodilla leaf extract , Minimun Inhibitory Concentration (MIC), and Staphylococcus aureus